Modification of Surface Roughness and Area of FeCrAl Substrate for Catalytic Converter using Ultrasonic Treatment - Putrasari, Yanuandri; Untoro, P; Hasan, Sulaiman; Huda, Naili; Sebayang, Darwin (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
Surface roughness and area play important role especially in deposition and reaction of the catalyst in the catalytic converter substrate. The aim of this paper is to show the modification of surface roughness and area of FeCrAl substrate for catalytic converter using ultrasonic method. The method was conducted by agitating the FeCrAl in 10 minutes 35 kHz ultrasonic cleaning bath. TheÂ  surface roughness, morphology, and chemical components of FeCrAl catalytic converter substrate after ultrasonic treatment were analyzed using atomic force microscope (AFM) and examined with scanning electron microscope (SEM) in combination with energy dispersive X-ray spectroscopy (EDS). The ultrasonic treatment assisted with Al2O3 powders successfully increased the roughness and surface area of FeCrAl better than SiC powders.Â